Bioorthogonally activatable cyanine dye with torsion-induced disaggregation for in vivo tumor imaging - Zhang, Xianghan (2023)
Advancement of bioorthogonal chemistry in molecular optical imaging lies in expanding the repertoire of fluorophores that can undergo fluorescence signal changes upon bioorthogonal ligation. However, most available bioorthogonally activatable fluorophores only emit shallow tissue-penetrating visible light via an intramolecular charge transfer mechanism. Herein, we report a serendipitous "torsion-induced disaggregation (TIDA)" phenomenon in the design of near-infrared (NIR) tetrazine (Tz)-based cyanine probe. The TIDA of the cyanine is triggered upon Tz-transcyclooctene ligation, converting its heptamethine chain from S-trans to S-cis conformation. Thus, after bioorthogonal reaction, the tendency of the resulting cyanine towards aggregation is reduced, leading to TIDA-induced fluorescence enhancement response. This Tz-cyanine probe sensitively delineates the tumor in living mice as early as 5 min post intravenous injection. As such, this work discovers a design mechanism for the construction of bioorthogonally activatable NIR fluorophores and opens up opportunities to further exploit bioorthogonal chemistry in in vivo imaging.